A SERLINE-based union list of serials for basic health sciences libraries: a detailed protocol. - Bell, C L (1982)
In March 1981 the Consortium for Information Resources (CIR) was chosen by the Massachusetts Health Sciences Library Network to develop and automate a statewide biomedical union list of serials. Employing a commercial processor, ANSI standard Z39.42-1980, and SERLINE, CIR consolidated the journal holdings of six Massachusetts health-related library consortia. SERLINE, with its unique identifier as the single control element, governed the form of entry and bibliographic data for each journal. Additionally, SERLINE enhanced the union list by providing "see references" and general notations to map users to main titles or special information. An original feature of this union list is the "rolled" holdings and location statements intended to encourage even distribution of interlibrary loan transactions. The resulting union list of serials includes the holdings of 116 Massachusetts libraries, 94 of which are hospital libraries. The list includes nearly 3,000 unique titles and 15,000 holdings statements; production costs averaged $1.35 per unique title and 27 per holdings statement.